A new genus and species of Parthenopidae MacLeay, 1838 (Decapoda: Brachyura) from the lower Eocene of Spain. Issue 3 (1st May 2019) - Ferratges, Fernando A; Zamora, Samuel; Aurell, Marcos
Abstract: We describe Aragolambrus collinsi n. gen., n. sp. from the Eocene (Ypresian) of Huesca, Aragón, northern Spain, which represents the second report of a fossil Parthenopidae from Spain and the first from the Eocene. Aragolambrus collinsi n. gen. n. sp. is considered one of the oldest parthenopid crabs, and important morphological features include the shape and size of tubercles of the proto- and mesogastric lobes and the morphology and ornamentation of the chelipeds. The shape of the carapace and orbits of the new species are similar to other Parthenopidae and the distribution and number of the tubercles of the inner margin of the manus suggest inclusion in the subfamily Daldorfiinae. Aragolambrus collinsi n. gen., n. sp. occurred in coral-algae reefs associated with a rich benthic biota of corals, red algae, echinoderms, molluscs, crustaceans, and fishes within the mesophotic zone. A review of all parthenopid Eocene occurrences suggests that the group originated in reef environments and later occupied more open marine conditions with siliciclastic substrates.